A Legal And Sosiological Analysis Of Trademark Circulation In Indonesia - Gilang Adi Febrian; Fajri Arie Firmansyah; Bayu Lesmana Prayoga; Diky Dikrurahman; Deni Yusup Permana (PT Publikasiku Academic Solution, 2024)
Intellectual property rights are a system of modern life that is interconnected with the system that exists today. Intellectual property rights are a by-product of human ideas and thought patterns, so they are currently one of the complex problems that arise in the world of commerce. The aim of this research is to analyze the sociology of law in the circulation of trademarks in Indonesia. Analytical descriptive methods are used in research specifications to describe facts and realities relating to trademark law in Indonesia. The research results show that, within the framework of the rule of law, respect for trademark rights is a national honor given to individuals who have taken the time to consider developing original and distinctive works of intellectual property. Legal sociology has a role in violations that occur in trademark cases; apart from filing criminal and civil charges for failure to reach a resolution, there are other options to overcome existing problems. All parties must comply with certain requirements so that the conflict resolution process can be effective. Having a certificate is one of the components of feeling more comfortable running a business in the future. It is easier for trademark owners to demonstrate ownership rights to the trademarks they use, so they don't need to worry about their company if a lawsuit occurs. Based on the results of the analysis carried out, society, namely the private sector, must support intellectual property, including trademarks, by upholding corporate ethics that demand integrity in all business dealings. Strong business growth in terms of market share and product quality is a catalyst for economic expansion, raising living standards, and achieving economic development.